Konsep Business Process ReenginEering untuk Memperbaiki Kinerja Bisnis Menjadi Lebih Baik: Studi Kasus Perusahaan Susu Kedelai âXYZâ - Wimpertiwi, Dotty; Sasongko, Agung Hari; Kurniawan, Antonius (Binus Business Review, 2014)
Business Process Reengineering is a phase of redesigning business process to improve performance. Business Process Reengineering can be applied to improve micro or medium businesses. One example from them comes from a soymilk company. XYZ Soymilk Company is one of the examples of Small and Medium enterprises with home-industry system. Its organizational structure consists of the director and some divisions. Those divisions, which are run by employees, are: production division, procurement division, finance division, and marketing division. The produced soymilk is packed in plastic bags with Susu Kedelai âXYZâ label on it. This product later is marketed in the canteens of universities, some stores around neighborhoods, and supermarkets. The main market target of this product is university students and people around the location. The promotion is done by attaching promotion flyers on some strategic places. The problem that occurs is a shortage in operational management, the number of command and control in the operating system, as well as recording done still manually. The purpose of using Business Process Reengineering concept processing system is to be more computerized for a better, faster, more accurate, effective and efficient, and improvement in operation management system as an attempt to survive among other competitors. The results of the business process reengineering are some business process ideas.